Association between obesity and periodontal disease in young adults: a population-based birth cohort - Dickie de Castilhos, Eduardo (Blackwell Publishing Ltd, 2012)
AIM: To evaluate the association between obesity and periodontal disease and the mediating effect of oral hygiene, systemic inflammation and carbohydrate intake. MATERIAL AND METHODS: Subjects born in 1982 in Pelotas, Brazil (n = 5,914), have been followed for several times. Oral health was assessed in a representative sample of 720 individuals at 24 years. Obesity, waist circumference and number of episodes with obesity between 15 and 23 years of age were the main exposures. Mediating effect of oral hygiene, C-reactive protein level and carbohydrate consumption was also assessed. RESULTS: Obese individuals were more likely to have ≥2 teeth with gingival bleeding. However, after adjusting for confounders, the association was not statistically significant [OR (obese × 2 or more teeth) 1.72 (95% CI: 0.95, 3.11)] and adjustment for potential mediators decreased the OR (OR = 1.38). The risk of presenting calculus in obese subjects was 10% higher [PR 1.10 (95% CI: 1.02, 1.18)]. The number of episodes of obesity between 15 and 23 years was associated with dental calculus. Periodontal pockets were not associated with obesity. CONCLUSION: Systemic inflammation and oral hygiene may be mediating the association between obesity and gingivitis. Obesity was not associated with periodontal pockets in young adults in this cohort.